Intrahepatic NK cells function suppressed in advanced liver fibrosis. (20th September 2016) - Li, Xiaoyan; Zhang, Min; Liu, Jing; Huang, Zhanlian; Zhao, Qiyi; Huang, Yuehua; Li, Xu; Gao, Zhiliang
Abstract: Background: Although numerous epidemiological studies indicate that hepatitis B virus‐related liver fibrosis (HBV‐LF), particularly cirrhosis, represents the main risk factor for liver cancer development, the mechanisms determining the persistence of fibrosis and liver cancer pathogenesis are still poorly defined. Few studies have investigated the status of NK cells during different stages of HBV‐LF. Methods: Liver tissues at least 3 cm away from the tumour site and peripheral blood were obtained simultaneously from 32 HBV‐infected patients undergoing surgery for HCC at the medical centre of Sun Yat‐sen University. We detected the amount of NK cells and analysed the phenotype and function of NK cells by flow cytometry. Results: We found that there was no difference in the amount of circulating and intrahepatic NK cells between early and advanced HBV‐LF. However, NKp46 expression on intrahepatic NK cells decreased and productions of IFN‐γ and perforin of intrahepatic NK cells declined apparently in patients with advanced HBV‐LF. Conclusion: In the present study, we displayed that in patients with advanced HBV‐LF, the expression of NKp46 on intrahepatic NK cells as well as productions of IFN‐γ and perforin of intrahepatic NK cells decreased significantly. These results indicated that the immune function of intrahepatic NK cells in patients with advanced HBV‐LF was suppressed distinctly, which provided new insight into the potential role of NK cells in the persistence of fibrosis and into the occurrence of HCC following cirrhosis.